New Sharp Error Bounds for Some Corrected Quadrature Formulae - Liu, Zheng (Sarajevo Journal of Mathematics, 2024)
A generalization of the pre-Grüss inequality is used to derive a new sharp L_2 inequality which provides improved versions of some corrected inequalities that appear in the literature. An application to numerical integration is illustrated. 2010 Mathematics Subject Classification. 26D15